2018
DOI: 10.1111/jgh.14438
|View full text |Cite
|
Sign up to set email alerts
|

Serum Mac‐2 binding protein glycosylation isomer predicts the activation of hepatic stellate cells after liver transplantation

Abstract: Mac-2 binding protein glycosylation isomer is a novel liver fibrosis marker in LT recipients and is also increased in patients with acute liver injuries, especially acute cellular rejection, even when fibrosis is absent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…M2BPGi increased in stages, as graft liver fibrosis progressed to a high degree. Further, in children, a correlation between post‐transplant liver fibrosis and M2BPGi has been reported by Yamada et al 21 The AUROC for diagnosis of F ≥ 2 in M2BPGi was 0.778, which was superior to Fibroscan and Fib‐4 index (Table 2). Therefore, the diagnostic performance of M2BPGi was comparable to other non‐invasive markers.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…M2BPGi increased in stages, as graft liver fibrosis progressed to a high degree. Further, in children, a correlation between post‐transplant liver fibrosis and M2BPGi has been reported by Yamada et al 21 The AUROC for diagnosis of F ≥ 2 in M2BPGi was 0.778, which was superior to Fibroscan and Fib‐4 index (Table 2). Therefore, the diagnostic performance of M2BPGi was comparable to other non‐invasive markers.…”
Section: Discussionmentioning
confidence: 54%
“…M2BPGi level was higher in the additional biopsy subgroup compared with the protocol‐biopsy subgroup ( P < .012). Previous reports have shown that M2BPGi level may be affected by inflammation 26 and post‐LT rejection is associated with M2BPGi 21 . Therefore, when considering rejection or under special circumstances, a biopsy may be more informative.…”
Section: Discussionmentioning
confidence: 99%
“…However, our study was more extensive, as we included more publications, had different subgroup setups, and used different models for the calculation of pooled results. WFA+-M2BP has the potential to reflect hepatic fibrosis as hepatic stellate cells (HSCs) are the source of WFA+-M2BP and its level is closely associated with α-smooth-muscle actin (αSMA) expression 19,21 . However, HBV-positive patients are more likely to experience quiescent hepatic inflammation, and HBV-related cirrhosis had large regenerative nodules and thin fibrous septa 23,27 .…”
Section: Discussionmentioning
confidence: 99%
“…In liver, WFA+-M2BP could promote fibrogenesis by acting as an important messenger between HSCs (secrete WFA+-M2BP) and Kupffer cells (express the ligand of M2BP, Mac-2) 18,19 . Additionally, WFA+-M2BP could be increased by TGF-β1 in LX-2 cell and it correlates with serum IP-10 and sICAM-1 levels in patients with AIH 20,21 . Those evidences suggested serum WFA+-M2BP has a great potential to serve as a biomarker for reflecting the liver status of CLD patients 16,22 .…”
mentioning
confidence: 91%
“…Activated HSCs in these situations may have a high potential to secrete M2BPGi. Indeed, it was reported that M2BPGi was increased in liver transplant patients with acute cellular rejection, even when fibrosis was absent . Furthermore, Morio et al reported that serum M2BPGi values were associated with clinical outcomes such as acute liver failure, development of hepatic coma, liver transplant, and death, suggesting that M2BPGi might reflect the severity of liver injury.…”
Section: Discussionmentioning
confidence: 99%